2014
DOI: 10.1002/anie.201409830
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Mediated Recognition of Simple Alkyl Chains by Heart‐Type Fatty‐Acid‐Binding Protein

Abstract: Long-chain fatty acids (FAs) with low water solubility require fatty-acid-binding proteins (FABPs) to transport them from cytoplasm to the mitochondria for energy production. However, the precise mechanism by which these proteins recognize the various lengths of simple alkyl chains of FAs with similar high affinity remains unknown. To address this question, we employed a newly developed calorimetric method for comprehensively evaluating the affinity of FAs, sub-Angstrom X-ray crystallography to accurately dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 21 publications
7
55
0
Order By: Relevance
“…To overcome this problem, we developed a method to comprehensively analyze FAs with long acyl chains. We used liposomes to mimic the physiological environment and make the long‐chain FAs (LCFAs) available to FABP3 (Figure a) . Our isothermal titration calorimetry (ITC) experiments clearly exhibited heat release upon binding of oleic acid to FABP3 (Figure b).…”
Section: Lipid–protein Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this problem, we developed a method to comprehensively analyze FAs with long acyl chains. We used liposomes to mimic the physiological environment and make the long‐chain FAs (LCFAs) available to FABP3 (Figure a) . Our isothermal titration calorimetry (ITC) experiments clearly exhibited heat release upon binding of oleic acid to FABP3 (Figure b).…”
Section: Lipid–protein Interactionsmentioning
confidence: 99%
“…FABP3 shows a clear preference for binding SFAs with C10–C18 chain lengths. The affinities for C10 and C18 were more than tenfold higher than for C8 and C20, respectively, and we were intrigued by this broad but specific substrate selectivity for C10–C18 chain length SFAs.…”
Section: Lipid–protein Interactionsmentioning
confidence: 99%
“…28,29 Purity was verified using sodium dodecyl sulfate polyacrylamide electrophoresis. Chicken eggwhite lysozyme (LZM) was purchased from Seikagaku Kogyo and used without further purification.…”
Section: Protein and Hydrogel Preparationsmentioning
confidence: 99%
“…[4][5][6] Many studies have investigated the role of water in protein-ligand interactions by examining the association of model proteins with sets of structurally varied ligands. [7][8][9][10][11][12][13][14][15] Such studies have revealed how the thermodynamic influence of water can differ between binding processes (e.g., the entropy-driven association of nonpolar ligands with the "well-hydrated" S3/4 pocket of thrombin, [7] or the enthalpy-driven binding of nonpolar molecules to the "poorly hydrated" cavity of mouse major urinary protein [8] ); they have not, however, illuminated the thermodynamic consequences brought about by systematic changes in the organization of water within a single pocket. An examination, thus focused, could reveal how different hydration/rehydration processes alter the thermodynamic mechanisms by which-and overall affinities with which-proteins and ligands associate.…”
Section: Introductionmentioning
confidence: 99%